Analysis of quantitative investment strategies - age-related investing: is firm age a good predictor of future stock returns - Alves, João David Vieira (2023)
This study analyses the impact of constructing a quantitative investment strategy based on information regarding firm age. The strategy is constructed based on the view that younger companies tend to outperform their peers, an idea that is verified by the performance results of the strategy. Additionally, the study goes one step further and analyses the impact of combining this information with information regarding the firms’ R&D investment policiesinto a combined information set, then used to construct an additional strategy, whose performance reveals that this combination generates significant returns.